Near to One's Heart: The Intimate Relationship Between the Placenta and Fetal Heart - Camm, Emily J.; Botting, Kimberley J.; Sferruzzi-Perri, Amanda N. (Frontiers in Physiology, 2018)
The development of the fetal heart is exquisitely controlled by a multitude of factors, ranging from humoral to mechanical forces. The gatekeeper regulating many of these factors is the placenta, an external fetal organ. As such, resistance within the placental vascular bed has a direct influence on the fetal circulation and therefore, the developing heart. In addition, the placenta serves as the interface between the mother and fetus, controlling substrate exchange and release of hormones into both circulations. The intricate relationship between the placenta and fetal heart is appreciated in instances of clinical placental pathology. Abnormal umbilical cord insertion is associated with congenital heart defects. Likewise, twin-to-twin transfusion syndrome, where monochorionic twins have unequal sharing of their placenta due to inter-twin vascular anastomoses, can result in cardiac remodelling and dysfunction in both fetuses. Moreover, epidemiological studies have suggested a link between placental phenotypic traits and increased risk of cardiovascular disease in adult life. To date, the mechanistic basis of the relationships between the placenta, fetal heart development and later risk of cardiac dysfunction have not been fully elucidated. However, studies using environmental exposures and gene manipulations in experimental animals are providing insights into the pathways involved. Likewise, surgical instrumentation of the maternal and fetal circulations in large animal species has enabled the manipulation of specific humoral and mechanical factors to investigate their roles in fetal cardiac development. This review will focus on such studies and what is known to date about the link between the placenta and heart development.